Fish fauna from Río Pilcomayo National Park and Ramsar Site and its surroundings, Formosa, Argentina - Brancolini, Florencia (2014)
The first list of fish species from the Río Pilcomayo National Park and Ramsar Site (RPNP), located in the WetChaco plains of Northern Argentina is presented here. Samplings were carried out bimonthly from December 2006 to January 2008 in sites representative of the different landscapes, in both dry and wet seasons. A total of 77 species were collected, belonging to 23 families and eight orders and covering 54% of the province ichthyofauna. New records to the Province of Formosa are Brachyhypopomus gauderio Giora & Malabarba, 2009; Cyanocharax sp. and Hypophthalmus edentatus Spix & Agassiz, 1829.